A Study on High Performance Generator Transfer System with Grid Connection and UPS - Yang, Ji-Hoon; Le, Tuan-Vu; Lee, Sang-Hun; Park, Seong-Mi; Park, Sung-Jun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently, the safety of the grid has been deteriorated due to the increase of the equipment using the stationary power converter, and the system accident such as power outage is increasing. Therefore, in recent years, there has been a surge in demand for systems that can supply stable power even if system accidents occur.Methods/Statistical analysis: The virtual coordinate conversion value obtained by converting the generator voltage to the rotational coordinate system based on the phase angle information based on the UPS voltage is obtained for linking the emergency generator with high accuracy. Then, it controls the Gabon and AVR of the generator to estimate the d-q voltage on the rotating coordinate system based on the phase angle information based on the UPS voltage. Therefore, when the d-axis component on the virtual rotation coordinate system is controlled to be 0, the generator voltage frequency becomes equal to the grid voltage frequency. If the q-axis component of the virtual rotation coordinate system is controlled by the q-axis voltage of the system rotation coordinate system, the generator voltage and the grid voltage become equal. To detect the switching point, I have improved the degree of voltage detection using a method of detecting the difference in magnitude and phase difference between different power sources. In order to compensate the fluctuation of the generator frequency when the load of the stand-alone generator suddenly changes, an algorithm that detects the active power instantaneously and performs feedforward control using it is applied.Findings: The proposed algorithm improves the voltage detection accuracy by detecting the difference of the dissimilar power source in order to detect the size and the phase difference to a high degree in the dissimilar power source. In addition, after controlling the d-axis voltage of the rotating coordinate system to 0, CTTS was injected to drastically reduce the inrush current. When the CTTS were shut off, the zero-current implementation through the instantaneous effective and reactive power control enabled us to stabilize the no arc and the system.Improvements/Applications: It has also been found that this system can be used not only as a UPS, but also as a reactive power compensator for system voltage stabilization.Â Â
Keywords: CTTS; ATS; Stable transfer; Diesel-engine generator; zero power control